PENGARUH TASK TECHNOLOGY FIT DAN EFFECTIVENESS ACCOUNTING INFORMATION SYSTEMTERHADAP KUALITAS KINERJA KEUANGAN DENGAN BALANCED SCORECARDSEBAGAI VARIABEL MODERETING - Irmadani, Irmadani; Muchlis, Saiful; Juardi, Sapril Sardi (JRAK (Jurnal Riset Akuntansi dan Komputerisasi Akuntansi), 2019)
This study aims to examine the effect of task technology fit and effectiveness accounting information system on the quality of financial performance with the balanced scorecard as a moderating variable. This research was conducted at PT. Perkebunan Nusantara XIV in the city of Makassar. This study is a quantitative research with a descriptive approach. The sampling technique used purposive sampling method, with 36 respondents as respondents. Data analysis using multiple linear regression analysis and moderation regression analysis (MRA).            The results of multiple linear analysis shows that technology fit task has a positive effect and the effectiveness accounting information system has a positive effect on the quality of financial performance. Moderation regression analysis shows that the balanced scorecard is able to moderate task technology fit the quality of financial performance, while the balanced scorecard is not able to moderate the effectiveness of accounting information system on the quality of financial performance.